Pengembangan Tutorial Digital Conducting untuk Mahasiswa PGSD - Andika Gutama; Arief Rahman Hakim (Universitas Kanjuruhan Malang, 2022)
The purpose of this study was to determine the feasibility, activity, practicality, and effectiveness of the product. This development process uses a 4D research model with the stages of defining, planning, developing, and distributing. The development of a digital conducting tutorial was declared feasible after going through the validation and testing process on students with a percentage of material experts 95% with very decent criteria, percentage of media experts 92.5% with very decent criteria. Products based on student activity questionnaires obtained a percentage of 94.5% with very active criteria and an assessment of student responses that obtained a percentage of 92.5% with very practical criteria. The digital conducting tutorial product for PGSD students was declared effective based on the average score of 32 students at 93.12 in the very effective criteria